Peculiarities of Traumatic Experience and Posttraumatic Growth of Adolescents and Young Adults During Wartime - Kuzikova , Svitlana; Yalanska , Svitlana; Lukomska , Svitlana; Fomenko , Karyna (Insight: the psychological dimensions of society, 2025)
The aim of the research is to identify the psychological characteristics of traumatic experience and posttraumatic growth of adolescents and young adults during wartime. Methods. A comparison of traumatic experience and stress tolerance of adolescents and young adults was carried out. The total sample included 151 individuals, of whom female (n = 78; 51.66%) and male (n = 73; 48.34%). In the age range, we have the following distribution: from 10 to 12 years old (n = 48; 31.79%), from 13 to 15 (n = 52; 34.44%), and from 16 to 17 years old (n = 51; 33.77%). Participants described their traumatic events using the PTSD symptom questionnaire “PCL–5” (Blevins et al., 2015), “Posttraumatic Growth Questionnaire” (Tedeschi, Calhoun, 1996), and “Meaning of Life Questionnaire” (Steger et al., 2006). The presence of a traumatic event (criterion A according to the posttraumatic stress disorder method “PCL–5”), which was found in 91.39% of respondents, was important for our study. Results. Among the traumatic events, the most common were the death of relatives and friends and injuries. It was found that deaths and injuries have become common phenomena in war conditions. They are perceived as individual grief, but due to their mass nature, they are not considered a collective tragedy (as was the case after the de-occupation of Kyiv, Kharkiv, and Kherson regions). According to the results of the diagnosis, PTSD was detected in 12.78% of the studied sample, which is generally consistent with the general world data in this field, including children, adolescents, and adults. Conclusions. The presence of a traumatic event and the severity of individual PTSD symptoms does not indicate PTSD as a medical diagnosis, not the least role in this is played by stress resistance and posttraumatic growth with the creation of new meanings of traumatic events. It is explained that after the end of hostilities, the situation may change and the so-called delayed PTSD will be actualized. A low level of posttraumatic growth was found in younger adolescents and a moderate level in older adolescents and young adults. It can be assumed that the indicators of posttraumatic growth will change over time after the trauma and will depend on the course and duration of war-time.
Keywords: psychological trauma; life crisis; mental health; mental state; self-regulation; psychological support